Pengembangan Bank Sampah Sebagai Salah Satu Solusi Pengelolaan Sampah Anorganik Di Kelurahan Kandri Kecamatan Gunungpati - Carina Sarasati; Tri Susetyo Andadari; Taufiq Rizza Nuzuluddin; Maria Rosita Maharani; Adi Sasmito (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
To create a clean tourist village, the people of Kandri Village carry out waste management using the 3R system (reduce, reuse, recycle). This system takes the form of a waste bank that effectively manages inorganic waste while providing economic benefits for the surrounding community. One of the active waste banks in Kandri Village, Gunungpati District is the